Design Of An Engine Using Hydrogen Fuel Derived From Biomass Gasification - Agusrianto, Yohn Hendra (Universiti Sains Malaysia, 2005)
Hydrogen is seen as one the important energy vector of next century. Hydrogen as an energy carrier provides the potential for a sustainable development of new engines. A hydrogen fueled engines has a potential for substantially cleaner emissions than other internal combustion engines. The hydrogen fueled engine is being developed into a hydrogen fueled engine with manifold injection, direct injection in cylinder, or dual injection according to the fuel supply method. A four stroke spark ignition (SI) engine was used for conducting this system. Hydrogen used in this engine is obtained from biomass gasification. Biomass system gasification results in conversion of carbonaceous materials to permanent gases, char and tar. There are many ways of biomass thermochemical process such as pyrolisis and gasification using either with air or steam. Catalytic biomass system is used in order to get rich hydrogen. Development of hydrogen fueled engine will become an alternative choice for future application.